Corporeal Commotions: St Faustina and the Transnational Evolution of her Cult across the Twentieth Century - Harris, Alana (Journal of religious history, 2018)
This article provides the first scholarly exploration of the hagiographical representations and modern mysticism of St Faustina a Polish nun who from 1931 had a series of visions of Christ who instructed her to have a devotional image painted and to institute a series of rosary-based prayers. It examines the visual, material, and corporeal practices associated with the transnational cult to the Merciful Heart of Jesus and excavates the ways in which the embodied and holistic intercessory strategies employed within this important strand of contemporary Catholic spirituality parallel, but also extend upon, the well-established seventeenth-century devotional to the Sacred Heart of Jesus. It argues that the cult's theological flexibility and practical malleability, alongside the premium on corporeality within contemporary religiosity, has ensured its delocalisation from its Polish genesis and adoption well beyond the Polish diaspora. Drawing upon the lived religious experiences of a number of St Faustina's clients, often centred on healing and the dying, and exploring the evolving devotion to the saint through shrines as well as online, this article illuminates the contemporaneous and traditional impulses at play within this new extra-liturgical, which has been designated "the most dynamically developing devotion in the Christian world."